Kajian Teologis Kolose 2:8 Sebagai Larangan Iman Kristen Tidak Berfilsafat - Waruwu, Vanny Miracleson; Yosef, Hery Budi (Pusat Studi Pentakosta Indonesia, 2023)
Humans are thinking creatures, and every human being is created with a ratio or reason. With the existence of ratios humans gain knowledge and knowledge that leads to new introductions and the desire to explore. In the pastoral ministry carried out by Epaphras, there was a problem, where the church in Colossae seemed to be infiltrated by false teachings that threatened the spiritual life of the church (Col 2:8). This threat is seen in his letter in Colossians 2:8 which states